Local authorities e - budget system - Chabata, Nyaradzo (Midlands State University, 2020)
Local authorities E-budget system is designed for the ministry of local governance head to facilitate generation and transfer of budgets. This system comprises of two users which are administrator and subordinates who are working in the town councils. These subordinates are responsible for budget generation, viewing generated budgets and assessment of the needs to be included in the budgets. Administrator is responsible for budget generation also, for his/her own council, approval of budgets is also his/her responsibility, disapproval of budgets as well is another responsibility of the administrator, management of users, that is adding, deleting, updating user database is also the other major responsibility for the administrator, back of database to ensure security of company information is also another action that administrator is responsible for, adding of new arising local authorities, this may happen if there is an added town council in the system boundaries. E-budget system comprises of these objectives. Starting with the major one, E-budget system is responsible for generation of budgets this may be done by subordinates, the second objective is approval of budgets generated by the chief accountant who is identified administrator in the system, third of objective is the disapproval of unauthorised budgets by chief accountant again, the system also give notification of newly generated budgets by the subordinates so that chief accountant may see the new budgets need to be approved